Data transport applications using GFP. - Scholten, M.
An emerging generic framing procedure (GFP) standard defines a new data encapsulation protocol designed to accept and transport multiple protocols over metropolitan, storage, and wide area networks. Why is another data encapsulation method needed for transporting data traffic over WANs? How does GFP encapsulate data for transport? This article provides an introduction to data transport applications, reviews existing data transport options (e.g., ATM and HDLC), introduces GFP as a new data transport technology, and compares GFP transport to existing popular alternatives.
Keywords: SONET; Asynchronous transfer mode; Data communication; Data encapsulation; Local area networks; Optical fibre networks; Synchronous digital hierarchy; Transport protocols; Wide area networks